Sustainability of external imbalances : a critical appraisal - Herzberg, Angélique (Springer Fachmedien Wiesbaden Imprint: Springer Gabler, 2015)
Since the mid-1990s, sustainability of large and persistent current account positions have been attracting much attention from policy makers and economists alike. Alongside global imbalances, sustainability of imbalances within the euro area, which started widening shortly after the introduction of the euro, raised much concern. While there exists a large body of theoretical and empirical literature on sustainability of external imbalances, a systematic survey has been lacking so far. Angélique Herzberg fills this gap by examining a broad range of established sustainability measures concerning their applicability to the various global and intra-euro imbalances of the recent past. Furthermore, the author examines the existence of feedback effects from an economy´s net international investment position to its trade balance.  Contents Empirical Studies on the Validity of the Intertemporal Budget Constraint Dynamic Benchmarks of External Sustainability  Targets Teachers and Students of Economics and Business Economic Policy Advisors  The Author Angélique Herzberg obtained a PhD in Economics in 2013 from Heinrich-Heine-University, Düsseldorf. Her areas of specialization are international macroeconomics and finance.